2000
DOI: 10.1590/s0100-879x2000000500001
|View full text |Cite
|
Sign up to set email alerts
|

Nonconventional amide bond formation catalysis: programming enzyme specificity with substrate mimetics

Abstract: This article reports on the design and characteristics of substrate mimetics in protease-catalyzed reactions. Firstly, the basis of protease-catalyzed peptide synthesis and the general advantages of substrate mimetics over common acyl donor components are described. The binding behavior of these artificial substrates and the mechanism of catalysis are further discussed on the basis of hydrolysis, acyl transfer, protein-ligand docking, and molecular dynamics studies on the trypsin model. The general validity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…84,87,88 Recent studies of Bordusa's group showed that lysine-containing substrates as well as modified amino acid containing derivatives can act as effective acyl donors in such peptide synthetic steps. 87,88 This approach is particularly useful for developing environmentally friendly, efficient, and selective methods for peptide or peptide isosteres synthesis, and clostripain seems to be one of the best biocatalysts for such transformations, due to its versatility in accepting non-natural, chemically modified amino acid residues in its binding pockets. Thus, it is possible to obtain easily peptide isosteres for the synthesis of pharmacologically active, proteolytically stable derivatives.…”
Section: A Proteases Of the C10 C11 And C15 Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…84,87,88 Recent studies of Bordusa's group showed that lysine-containing substrates as well as modified amino acid containing derivatives can act as effective acyl donors in such peptide synthetic steps. 87,88 This approach is particularly useful for developing environmentally friendly, efficient, and selective methods for peptide or peptide isosteres synthesis, and clostripain seems to be one of the best biocatalysts for such transformations, due to its versatility in accepting non-natural, chemically modified amino acid residues in its binding pockets. Thus, it is possible to obtain easily peptide isosteres for the synthesis of pharmacologically active, proteolytically stable derivatives.…”
Section: A Proteases Of the C10 C11 And C15 Familiesmentioning
confidence: 99%
“…Thus, it is possible to obtain easily peptide isosteres for the synthesis of pharmacologically active, proteolytically stable derivatives. 87,88 Pyroglutamyl-peptidases, enzymes that remove the aminoterminal pyroglutamate (L-pyroglutamyl, Glp) residue from specific pyroglutamyl substrates, were isolated from mammalian and bacterial sources. 89 The enzyme was formerly classified as an aminopeptidase (EC 3.4.11.8), but is more accurately regarded as an omega peptidase, because the substrate contains no free aminoterminal NH 2 group.…”
Section: A Proteases Of the C10 C11 And C15 Familiesmentioning
confidence: 99%
“…Enzymes are versatile biocatalysts, serve as a key enabling technology for chemical synthesis and are considered as “green chemicals” due to their eco-friendly nature [6]. Proteases are the group of proteolytic enzymes which are capable of peptide bond hydrolysis but there is evidence that it can efficiently catalyze the peptide synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to kinetically controlled reaction thermodynamically controlled reaction is rather slow and gives lower yield. Under thermodynamic control, manipulation of reaction conditions are required to shift the equilibrium in the direction of amide synthesis instead of their hydrolysis by, product precipitation, water removal or addition of organic solvents to suppress the ionization of the starting materials [6], [14], [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…First, the carboxyl group of succinic acid is activated by phosphorylation or acylation, and is then attacked by the amino group of L-tyrosine to form the amide bond. The reaction can be catalyzed by specific enzymes such as amide synthetase, or by enzymes for non-peptide amide bond formation (Bordusa, 2000;Maruyama et al, 2012;Ladkau et al, 2011). In addition, proteases as catalysts are capable of accelerating the hydrolysis of peptide bonds in aqueous solution, as well as the synthesis of peptide bonds and non-peptide amide bonds in a small hydrophobic zone (Stepanov, 1996;Chen et al, 2010).…”
Section: Verification Of the Biosynthesis Precursors Of Related Substmentioning
confidence: 99%